Nghiên cứu hấp phụ anion nitrat từ dung dịch bằng nhựa trao đổi anion Lewatit monoplus M 500 - Nhiệm, Đào Ngọc; Dũng, Đoàn Trung; Hà Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
In the present study the sorption of nitrate anion from aqueous solution medium was investigated by using Lewatite Monoplus M 500. The effects of factors such as pH (from 1 to 10), nitrate anion concentration (from 0 mg/l to 4000 mg/l), sorption equilibrium times (from 2.5 minute to 15 minute) and sorption temperature (from 10 oC to 40 oC) have been studied. The results showed that the optimized conditions (pH = 6, sorption equilibrium time of 10 minute, sorption temperature of 30°C) for obtaining the maximum adsorption capacity nitrate anion of M 500 was 70.6 mg/g  with regression coefficient of 0.99. The experimental results demonstrated that M 500 anion exchange resin could used effectively for the removal of nitrate anion from aqueous solution medium.